Mahfūz al-Tirmisī (d. 1338/1919): An Intellectual Biography - Mas‘ud, Abdurrahman (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1998)
This paper describes the journey of intellectual Mahfouz al-Tirmisi as scholars who came from the farthest regions of the Islamic world, which ultimately able to develop themselves into well-known scholars in the Middle East and a lecturer in classical Islamic science center, Masjid al-Haram. Moreover, the success that Mahfouz has also contributed significantly in establishing the intellectual relationship between scholars archipelago with the Middle East. This also paved the way for the advancement of educational institutions of traditional Islam in Southeast Asia.DOI:Â 10.15408/sdi.v5i2.752